Conservation of selected legally protected and red-listed bryophyte species in Ireland - Campbell, Christina (Trinity College (Dublin, Ireland). Department of Botany, 2013)
This thesis focussed on the conservation of ten rare and threatened bryophyte species in Ireland using three separate, but complementary conservation approaches to provide an integrated strategy to ensure their survival into the future. The research focussed on in situ conservation and monitoring, the creation of ex situ conservation collections, including the ex situ investigation of experimental conservation case studies, and genetic fingerprinting analysis of selected species.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin.